Optimizing the Role of Nurses: Self-Efficacy and Nurse Effective Communication as the Key to Patient Satisfaction - Suhartini, Titik; Piesesha, Frieska; Ardiyanto Wibowo, Bima (AACENDIKIA: Journal of Nursing, 2025)
Self-efficacy is a crucial determinant affecting the quality of nursing care. Nurses who lack confidence in their ability to deliver quality patient care may precipitate unforeseen incidents that adversely affect the standard of nursing care (Nita & Agustika, 2023). Therapeutic Employee Performance is essential; it is a deliberately strategised and concentrated form of Employee Performance that seeks to facilitate the patient's recovery. All actions and communications from the nurse must be therapeutic for the patient. This study examines nurses' self-efficacy and therapeutic Employee Performance models regarding patient satisfaction. The employed research strategy is a correlational analysis using a cross-sectional design. The sample comprises 100 inpatients at Wijaya Kusuma Hospital, chosen through accidental sampling. The research variables include self-efficacy, therapeutic employee performance, and patient satisfaction. Data collection was conducted via questionnaires, and the data were processed through editing, coding, scoring, and tabulation steps. Subsequently, it underwent analysis using regression testing. The research revealed a P-value of 0.000, demonstrating a significant link among self-efficacy, therapeutic employee performance, and patient satisfaction. This strong association indicates that self-efficacy and therapeutic employee performance may significantly enhance patient satisfaction, thereby benefiting patient visits.